ENDOMETRIOSIS – AN AYURVEDIC DIAGNOSIS AND MANAGEMENT (AYUSHDHARA, 2020)
Motherhood is the greatest gift conferred to woman by God. Hence he created woman with different anatomical and physiological considerations when compared to man. Therefore unlike man, woman is subjected to various diseases mainly pertaining to her reproductive system. A few of these diseases may disturb her womanhood and a few may land her in life threatening conditions if not treated properly. One such disease is endometriosis. Endometriosis is a disease in which ectopic endometrial tissues are found outside the inner lining of the uterus. Patient experiences severe pain which may be gradually worsening. This ectopic endometrial tissue behaves as normal endometrial tissue and bleeds every month. This blood may become encysted and form chocolate cyst which may rupture also. At this stage surgical intervention is required or the life of the patient may be in threat. Hence a management which not only treats endometriosis but also prevents the chocolate cyst formation is highly essential. According to Ayurveda endometriosis can be compared to “Vyana Avruta Apana Vata” and has to be managed accordingly. Management principles include Amachikitsa, Vyana Avruta Apana Vata Chikitsa, and Samana therapies. Life style and diet modifications are also to be advocated as their role in the establishment of any disease cannot be ignored. Certain Ayuredic medicines possessing the above properties and are helpful in the clinical management of endometriosis will be discussed in this full paper.